2018
DOI: 10.20944/preprints201805.0064.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycorrhiza Fungus <em>Rhizophagus intraradices </em>Mediates Drought Tolerance in <em>Eleusine coracana</em> Seedlings

Abstract: Under abiotic stress conditions, arbuscular mycorrhizal (AM) fungi help plants by improving nutrient and water uptake. Finger millet is an arid crop having soils with poor water holding capacity. Therefore, it is difficult for the plants to obtain water and mineral nutrients from the soil to sustain life. To understand the role of mycorrhizal symbiosis in water and mineral up-take from the soil, we studied the role of Rhizophagus intraradices colonization and its beneficial role for drought stress tolerance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the existing studies, the results about the changes of proline of mycorrhizal plants under drought stress are inconsistent. Studies by Zhang et al [36] on Eriobotrya japonica and Tyagi et al [37] on Eleusine coracana showed that the roots of AM plants accumulated more proline versus non-mycorrhizal plants under drought stress, and lipid peroxides of mycorrhizal plants were less than non-mycorrhizal plants under drought stress.…”
Section: Osmotic Adjustment Substancesmentioning
confidence: 99%
“…In the existing studies, the results about the changes of proline of mycorrhizal plants under drought stress are inconsistent. Studies by Zhang et al [36] on Eriobotrya japonica and Tyagi et al [37] on Eleusine coracana showed that the roots of AM plants accumulated more proline versus non-mycorrhizal plants under drought stress, and lipid peroxides of mycorrhizal plants were less than non-mycorrhizal plants under drought stress.…”
Section: Osmotic Adjustment Substancesmentioning
confidence: 99%
“…Ascorbate and glutathione levels were recorded higher in Poncirus trifoliata trees colonized by Glomus versiforme in contrast to uninoculated trees during a drought period of 12 days [64]. Research studies in mycorrhizal ( Rhizophagus intraradices ) inoculated Eleusine seedlings revealed 16% higher flavonoid content and 25% higher ascorbate level in the leaves during drought stress [65]. In addition glutathione content was also recorded to be higher in AM inoculated seedlings.…”
Section: Microbe Mediated Biochemical and Metabolic Mechanisms To mentioning
confidence: 99%
“…Furthermore, improvement in the production of finger millet could be helpful in the food production systems in Asian countries (Thilakarathna and Raizada 2015). Improvement in plant growth, nutrition uptake, tolerance to drought, and metal toxicity in finger millet using different AM fungal species have been well documented (Patil et al 2013;Tyagi et al 2018). Moreover, Tewari et al (1993) investigated the potential of AM fungal species for improving the growth of five different cultivars of finger millet using six commercial nonindigenous AM fungal isolates individually in unrealistic sterilized soil conditions.…”
Section: Introductionmentioning
confidence: 99%